Legal Drugs Are Good Drugs And Illegal Drugs Are Bad Drugs - Dina Indrati; Herry Prasetyo (Diponegoro University, 2011)
ABSTRACT : Labelling drugs are important issue nowadays in a modern society. Although it is generally believed that legal drugs are good drugs and illegal drugs are bad drugs, it is evident that some people do not aware about the side effects of drugs used. Therefore, a key contention of this philosophical essay is that explores harms minimisation policy, discuss whether legal drugs are good drugs and illegal drugs are bad drugs and explores relation of drugs misuse in a psychiatric nursing setting and dual diagnosis. Key words: Legal, good drugs, illegal, bad drugs.